Current status of African swine fever - Mary Louise Penrith (CABI Agriculture and Bioscience)
Abstract African swine fever is a serious viral disease of domestic pigs and Eurasian wild boars that poses a major threat to pig production. For more than thirty years after its discovery in East Africa it was limited to eastern and southern Africa, where it is believed to have originated. The ability of the causative virus to remain viable for long periods in raw or insufficiently cooked pork products has enabled it, through travel and trade, to spread widely throughout sub-Saharan Africa and to other continents. In the second half of the 20th century it had caused outbreaks in the majority of African countries where pigs are produced, as well as in a number of European countries, two of the Caribbean islands, and Brazil. By the turn of the century it had been eradicated from all non-African countries except the Italian island of Sardinia. In 2007 African swine fever arrived in the Republic of Georgia, and has subsequently spread insidiously into other Transcaucasian countries, Russia and some of its neighbours. In 2014 it reached the Baltic States and Poland through infected wild boars, and has become established in several wild boar populations from which it is difficult to eradicate. Most recently, in 2018 the first outbreaks were reported in China, home to half of the world’s pig population, where it spread with unprecedented rapidity throughout China and to several other countries in the region, including the island nations of Philippines, Indonesia, Timor-Leste and Papua New Guinea. These events have posed new challenges for control, including some that parallel the situation in Africa, where poor people rely on pigs produced at subsistence level to provide for their needs and where pigs may also be socially and culturally important. The central role that humans play in the maintenance and spread of African swine fever has again been emphasised. This review describes the current status of African swine fever globally and the trends and challenges for management that face veterinarians and pig industries at all levels worldwide.